Analysis Of BPJS Drug Investment Management Using Activity-Based Cost (ABC) Method (Case Study in Ponorogo Health Office) - Yuniar, Cinthya Ratna; Widyaningsih, Linda; Indraswari; Yustyananingrum, Nora (Airlangga Journal of Innovation Management, 2025)
Medicines are an important component in ensuring health services. The Ponorogo City Health Service is the source of drug procurement for primary health services in Ponorogo. Procurement uses limited Regional Revenue and Expenditure Budget (APBD) funds, so studying the types of medicines most needed and the funds absorbed for procurement efficiency is necessary. This research aims to analyze the efficiency of item selection and use of BPJS drug procurement funds at the Ponorogo City Health Service. Observation period January to June 2023 using the ABC method. This research is included in the mixed research method qualitative and quantitative descriptive with retrospective data collection. The ABC method is used to identify priority items based on their contribution to costs, classifying A, B, and C based on use value and investment value. The research results showed 111 BPJS medicine items in the Ponorogo City Health Service. This study has theoretical implications by identifying uneven patterns of BPJS drug use and investment between groups. The finding that group A absorbs the most investment (70.62%) but only contributes 19.82% of the total goods, while group C has the highest percentage of the total goods (63.96%) but low contribution of use and investment (9.36% and 9.09%), indicates the need to revise the resource allocation model in the BPJS program. From a managerial perspective, this study recommends optimizing budget allocation, evaluating drug procurement policies, and improving the monitoring system to ensure program efficiency and effectiveness.